ANTI-PHISHING WITH GOOGLE EXTENSION 3H1M USING BLACKLIST ALGORITHM - Muhammad Hafiz Ramli, Ahmad Izatul Hisham Faugi, Nur Mawaddah Mohd Faizal, NorHaziqah Mohd Khadri, Jasni Mohamad Zain (Malaysian Journal of Computing, 2020)
The advancement of technologies has rapidly risen for the past few years, which brings a lot of benefits especially to the users. However, the developments have also contributed many security issues, where security attacks have also become more advanced. Phishing is one of the security attacks that describe spoof emails or websites to trick users into exposing their personal or any confidential information. Hence, this project develops a solution, 3H1M extension, to help in mitigating the phishing issues when browsing the Internet. This extension will compare the visited website URL with the blacklisted website lists in the database to identify the validity of the website. If the user is visiting a malicious website, a pop-up message will be displayed on the screen and the user will be directed to the search engine page. A comparison is made between a web browser implemented with and without the 3H1M extension. It can be observed that the extension is able to help the users to distinguish between the real and malicious websites.